2017
DOI: 10.17235/reed.2017.5114/2017
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal lesions detected during small bowel capsule endoscopy: incidence, diagnostic and therapeutic impact

Abstract: Juanmartiñena-Fernández JF, Fernández-Urién-Sainz I, Zabalza-Ollo B, Saldaña-Dueñas C, Montañés-Guimera M, Elosua-González A, Vila-Costas JJ. Gastroduodenal lesions detected during small bowel capsule endoscopy: incidence, diagnostic and therapeutic impact. Rev Esp Enferm Dig 2018;110 (2) ABSTRACTBackground: Capsule endoscopy was primarily designed for the investigation of the small bowel. However, it may also identify lesions in other segments of the gastrointestinal tract. The aim of the current study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Juanmartiñena Fernández et al[31] retrospectively analyzed data from 2217 consecutive SBCE performed in a tertiary centre in Spain between 2008 and 2016. 52.3% of the patients were referred for occult GI bleeding.…”
Section: Non-small Bowel Lesions Detected By Small Bowel Capsule Endomentioning
confidence: 99%
See 3 more Smart Citations
“…Juanmartiñena Fernández et al[31] retrospectively analyzed data from 2217 consecutive SBCE performed in a tertiary centre in Spain between 2008 and 2016. 52.3% of the patients were referred for occult GI bleeding.…”
Section: Non-small Bowel Lesions Detected By Small Bowel Capsule Endomentioning
confidence: 99%
“…52.3% of the patients were referred for occult GI bleeding. The rest were referred for Crohn’s disease, abdominal pain, chronic diarrhoea or other indications[31]. SBCE detected gastroduodenal lesions in 566 patients.…”
Section: Non-small Bowel Lesions Detected By Small Bowel Capsule Endomentioning
confidence: 99%
See 2 more Smart Citations
“…This is different from the results in adults, in whom obscure gastrointestinal bleeding is the main indication for VCE. [ 18 , 19 ] Recently, a systemic review reported that the pooled diagnostic yield of VCE for chronic abdominal pain was 20.9%; [ 20 ] Huang et al showed a 28.15% positive rate of VCE findings in the small bowel in chronic abdominal pain patients. [ 6 ] In this study, abdominal pain was the main indicator for VCE (54.1%), with 49.1% diagnostic yield in patients with chronic abdominal pain.…”
Section: Discussionmentioning
confidence: 99%